Medical service redesign shares the load saving 6000 bed days and improving morale. Issue 8 (August 2014) - Toomath, R.; Szecket, N.; Nahill, A.; Denison, T.; Spriggs, D.; Lay, C.; Wilkinson, L.; Poole, P.; Jordan, A.; Lees, J.; Millner, S.; Snow, B.
Abstract Background and Aims In 2010, demand on the Auckland City Hospital general medical service exceeded capacity. A review by the Royal Australasian College of Physicians was critical of training offered to registered medical officers, and low morale was a problem across the service. Management offered support for an improved model that would solve these problems. Methods A project to redesign the general medical service was undertaken. Baseline analysis found uneven workload and insufficient capacity at peak times for patient presentations. Workshops involving the entire service led to a new model that splits workload and teams into patients likely to have a short stay from those requiring longer, ward‐based care. Admissions are now distributed over 12 teams on weekdays and 4 on the weekends. There was an increase of approximately 2.5 in consultant full time equivalents but no change in registrar or house officer staffing. Results Since the introduction of the new model, the average length of stay has fallen from 3.7 to 3.2 days (14%) and the median length of stay by 28%, resulting in a saving of 6000 bed days per year. Readmission, inpatient and 30‐day mortality rates are unchanged. These results have been sustained over 18 months with signs of continuing improvement. Conclusion This project owes its success to the following factors – management support; iterative engagement of a range of staff; provision of timely data analysis; increases in senior medical officer staffing and reorganisation leading to more predictable and fair work practices. One challenge is discontinuity, whether between doctors and patients or within the medical team.